Praktik Pembuatan Rengginang Ubi Jalar Upaya Pemberdayaan Masyarakat Berbasis Potensi Lokal Di Desa Besakih Bali - Andriyanto, Gian Anggraeni; Prasetyawati, Andini; Pratiwi, Ni Luh Dian; Nursyamsyiah, Ai; Wulandari, Putri Aulia (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Besakih Village, which is located at the foot of Mount Agung, is known as a village with high cultural and historical value. Another potential is in the agriculture and plantation sectors. These potentials show that Besakih Village is not only rich in natural resources, but also has great opportunities in the development of the economic sector from its natural potential. Community service through the practice of making rengginang made from sweet potatoes aims to utilize the local potential of Besakih Village through the innovation of sweet potato-based processed food products. By using the Asssets-Based Community Development (ABCD) approach which emphasizes the use of local assets as the basis for sweet potato rengginang practice activities. The activity began with the identification of village potential through discussions with local residents online. The stages of the activity include socialization, manufacturing practices, and reflection or evaluation. The results of this community service show that the innovation of sweet potato-based rengginang was positively received by the women present because it provides an alternative to the management of innovative agricultural products from sweet potatoes which are usually processed in traditional foods. However, there are challenges in the drying process due to the rainfall that is quite dominating in Besakih Village. From the evaluation, it indicates that community involvement still needs to be increased to support the sustainability of innovation. The ABCD method used is effectively used to optimize local potential. However, its implementation requires support Furthermore, both in the form of advanced training, access to simple technology for drying, as well as institutional strengthening, and marketing so that this practice can be developed as MSME products based on local and community potential.